Functional Restoration of Bilateral Wrist Level Hand Amputee with Six-Toe Transfers and Three Free Flaps: An Alternative to Hand Allotransplantation or Prosthesis - Rajendra Nehete; Anita Nehete; Amol Ghalme; Abhishek Kulkarni; Al Iqyan Fidvi (Indian Journal of Plastic Surgery)
Introduction Hand amputation at the wrist level is severely disabling, especially when bilateral. It is paramount to restore the hand function to the best possible level for the patient's daily living activities, as well as optimal social and occupational rehabilitation. There are various options for restoration of function after amputation at wrist and distal forearm levels including Krukenberg's operation, variations of toe transfers, hand allotransplantation, and prosthesis. Krukenberg's procedure and the reconstruction using toe transfer like Vilkki's procedure or two-toe transfers, restore only the pinch. Hand allotransplantation, although it gives excellent function, has limitations due to the complications of immunosuppression. Functional hand prosthesis, though superior in cosmetic appearance, have again limitations in function, and the cost is prohibitive for most patients in our country.